2009
DOI: 10.1182/blood-2008-02-138172
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH is a key regulator of human T-cell acute leukemia initiating cell activity

Abstract: Understanding the pathways that regulate the human T-cell acute lymphoblastic leukemia (T-ALL) initiating cells (T-LiC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
163
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 156 publications
(170 citation statements)
references
References 39 publications
6
163
0
1
Order By: Relevance
“…7 NOTCH1, FBW7, and PTEN genomic loci were sequenced as described. 4,20,34,35 In vitro culture of primary T-ALL cells Primary human T-ALL cells were cultured either on MS5/MS5-DL1 stromal feeder cells as described, 7 or without feeders in plastic dishes coated with immobilized DL1 ligand (Delta1 ext-IgG , kind gift of Dr Irwin Bernstein, Fred Hutchinson Cancer Research Center) 36 at a concentration of 0.5 g/cm 2 . Primary mouse T-ALL cells were cultured without feeders or immobilized ligand in complete media with supplemental cytokines.…”
Section: Human Leukemia Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…7 NOTCH1, FBW7, and PTEN genomic loci were sequenced as described. 4,20,34,35 In vitro culture of primary T-ALL cells Primary human T-ALL cells were cultured either on MS5/MS5-DL1 stromal feeder cells as described, 7 or without feeders in plastic dishes coated with immobilized DL1 ligand (Delta1 ext-IgG , kind gift of Dr Irwin Bernstein, Fred Hutchinson Cancer Research Center) 36 at a concentration of 0.5 g/cm 2 . Primary mouse T-ALL cells were cultured without feeders or immobilized ligand in complete media with supplemental cytokines.…”
Section: Human Leukemia Samplesmentioning
confidence: 99%
“…All patient samples were obtained at initial diagnosis. We cultured human lymphoblasts in vitro on either MS5/MS5-DL1 feeders 7 or immobilized DL1 ligand 40 for 1 to 6 days prior to initiation of GSI treatment. Cultures were then exposed to GSI versus DMSO vehicle for a 4-day period and subsequently assayed for proliferation, cell size, and apoptosis ( Figure 4 and supplemental Figure 7).…”
Section: Primary Human T-all Cells Show No Correlation Between Pten Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental approaches that accurately identify the frequency and immunophenotype of LSCs are essential for appropriate conclusions to be drawn regarding disease biology and for the design of therapies that target the self-renewing compartment. In precursor T-acute lymphoblastic leukaemia (ALL), the frequency of LSCs (defined as cells that initiate leukaemic engraftment in a xenograft recipient) is reported to range from one in 10 5 -10 7 following intravenous injection into non-obese diabetic severe combined immunodeficient (NOD/SCID; NS) mice (Cox et al, 2007;Chiu et al, 2010), or one in 10 3 -10 5 where the more immunodeficient NOD.Cg-Prkdc scid Il2rg tm1Wjl /SzJ (NSG) strain is used (Armstrong et al, 2009;Chiu et al, 2010). In precursor B-ALL, NS xenograft-initiating cell frequencies of one in 10 5 -10 7 have been reported (Cobaleda et al, 2000), with higher frequencies observed following intrafemoral transplant into NSG mice (one in 40-10 3 ; le Viseur et al, 2008;Rehe et al, 2013) or where cells from chemorefractory patients are used (one in 10-10 2 ; Morisot et al, 2010).…”
Section: Very High Frequencies Of Leukaemia-initiating Cells In Precumentioning
confidence: 99%
“…Cependant, il serait hasardeux d'extrapoler des résultats obtenus à partir de lignées cellulaires perpétuées en culture depuis des années à des cellules de patients au diagnostic. Au cours des derniè-res années, nous avons développé des modèles expérimentaux de culture, de greffe et de modification génique des LAL-T humaines à partir de cellules de patients [11,12], modèles qui permettent à présent d'explorer des questions relatives à la régulation moléculaire du développement leucémique. En utilisant ces outils, nous avons montré la dépen-dance des LAL-T primaires vis-à-vis des niveaux d'expression de TAL1 et de NKX3.1 puisqu'une diminution drastique de l'expression de TAL1 ou de NKX3.1 compromet la croissance des cellules leucémiques en culture et le développe-ment leucémique dans des souris immunodéficientes, tandis qu'une diminution partielle n'altère que peu ces caracté-ristiques.…”
Section: Nkx31 La Cible Inattendue De Tal1 Dans Les Lal-t Humainesunclassified